Revealing Geometry and Fault Interaction on a Complex Structural System Based on 3D P-Cable Data: The San Mateo and San Onofre Trends, Offshore Southern California - Holmes, James J.; Perea, Hector; Driscoll, Neal W.; Kent, Graham M. (Frontiers in Earth Science, 2021)
Compressional deformation observed along the San Mateo (SMT) and San Onofre trends (SOT) in southern California has been explained by two opposing structural models, which have very different hazard implications for the coastal region. One model predicts that the deformation is transpressional in a predominantly right lateral fault system with left lateral step-overs. Conversely in the alternative model, the deformation is predicted to be compressional associated with a blind thrust that reactivated detachment faults along the continental margin. State-of-the-art 3D P-Cable seismic data were acquired to characterize the geometry and linkage of faults in the SMT and SOT. The new observations provide evidence that deformation along the slope is more consistent with step-over geometry than a regional blind thrust model. For example, regions in the SOT exhibit small scale compressional structures that deflect canyons along jogs in the fault segments across the slope. The deformation observed in the SMT along northwesterly trending faults has a mounded, bulbous character in the swath bathymetry data with steep slopes (~25˚) separating the toe of the slope and the basin floor. The faulting and folding in the SMT are very localized and occur where the faults trend more northwesterly (average trend ~285˚) with the deformation dying away both towards the north and east. In comparison, the SOT faults trend more northerly (average trend ~345˚). The boundary between these fault systems is abrupt and characterized by shorter faults that appear to be recording right lateral displacement and possibly accommodating the deformation between the two larger fault systems. Onlapping undeformed turbidite layers reveal that the deformation associated with both major fault systems may be inactive and radiocarbon dating suggests deformation ceased in the middle to late Pleistocene (between 184 and 368 kyr). In summary, tectonic deformation along the SMT and SOT is best explained by left lateral step-overs along the predominantly strike-slip fault systems. The lack of evidence for a blind thrust underlying the southern California margin reduces the hazard for coastal regions because there would be no hanging wall effects during an earthquake and nearby slip rates would be reduced.